Pemahaman Hadis Tentang Poligami (Sebuah Kajian Teologis Terhadap Hadis-hadis Sosial tentang Poligami) - Safitri, Erwanda (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
In this article, the author tries to see about polygamy obey Islam. Poligamy is something always happens around human life. Issues of polygamy is very often discussed. Controversy about what is right and wrong fittingly never end. as written in the Qur’an has been widely described. However, the hadith of the Propet Muhammad as the highest authority after the Qur’an. In here the outhor will be include some text Qur’an and hadith was related trough the viewpoint of existing traditions in the book of tafsir. So it can be taken a cloncusion and results may provide additional insight into the solution and for all.Keywords: poligami, islam